Assessment of Compatibility of Common European Framework of Reference for Languages (CEFR) with the Educational System in Teaching European Languages at College of Languages and Translation, King Saud University (Applied to: The Program of French Language and Translation) - AlZahrani, Mohammad (Dirasat: Human and Social Sciences, 2021)
The aim of this study study is to explicitly point out the extent of compatibility of the key basics of the Common European Framework of Reference for Learning Languages with the system of study within the Program of European Languages and Translation at College of Languages and Translation, King Saud University, Riyadh. In his paper, the researcher reviewed the key constituents of the study system: such as curriculum, levels of study and the mechanism of course enrollment and had them all benchmarked with the foundations upon which CEFR levels, the graduation mechanism as well as the assessment strategies therein have been set. As such, the researcher tracked the academic records of a group of students at the Program of French Language and Translation over an extended period of four years. Based on these benchmarks, the researcher has concluded that the application of CEFR levels was flawed for sundry administrative and educational reasons; which ultimately led to the Framework being stripped away of its own goals. This has had subsequently a noticeable impact on the progress of the educational process and thus the level of student achievement. To confirm this, the researcher conducted a statistical analysis that has proven the presence of statistically significant variations at a level less than (0.001) in favor of the regular group in studying language courses (mean = 3.8607), compared to the irregular language course group (average =2.7603), where the result of the T test was t (6.961) =, p≤ (0.001).